Association Between Gamma-Glutamyl Transferase, Total Bilirubin and Systemic Lupus Erythematosus in Chinese Women - Zhang, Wenran; Tang, Zhaoyang; Shi, Yanjun; Ji, Long; Chen, Xueyu; Chen, Yanru; Wang, Xiaohui; Wang, Meng; Wang, Wei; Li, Dong (Frontiers in Immunology, 2021)
Background: Systemic lupus erythematosus (SLE) affects many organs and systems of the human, its pathogenesis is not completely clear, but inflammation is considered to be an important factor involved in the pathogenesis and progression of SLE. Gamma-glutamyl transpeptidase (GGT) and total bilirubin (TBIL) have different effects on inflammation: GGT has pro-inflammatory effects and TBIL has anti-inflammatory effects. Study has found GGT and TBIL play opposite roles in metabolic diseases. However, the roles of them in SLE are unknown. Method: We recruited 341 SLE patients and 332 healthy individuals in Liaocheng People’s Hospital from August 2018 to May 2019. We diagnosed SLE using 2019 revised American College of Rheumatology (ACR) SLE criteria, and modeled the study outcomes using logistic regression to explore the respective relationship between GGT, TBIL and SLE. We also analyzed the interaction of GGT and TBIL in the progression of SLE. Results: In the case group,according to Spearman correlation analysis, GGT is proportional to CRP (rs=0.417) and IL-6 (rs=0.412), inversely proportional to C3 (rs=-0.177) and C4 (rs=0.-132). TBIL was inversely proportional to CRP (rs=-0.328) and TNF(rs=-0.360), and positively proportional to C3 (rs=0.174) and C4 (rs=0.172). In the fully adjusted model, compared to the lowest quartile, the highest quartile of GGT exhibited a positive association with the risk of SLE aggravation (OR=3.03, 95% CI: 1.55–5.91, P<0.001) Meanwhile, compared to the highest quartile, the quartile lowest of TBIL exhibited a positive association with the risk of SLE aggravation (OR=2.63, 95% CI: 1.36–5.09, P<0.001) in the fully adjusted model. Through interaction analysis, we found that women with high GGT levels had an increased risk of SLE aggravation when they had a low level of TBIL (OR=3.36, 95% CI: 1.41,9.36, for women with Q1 TBIL and Q4 GGT compared to women with Q2-Q4 TBIL and Q1-Q3 GGT, P for interaction <0.001), Conclusion: We found that the effects of GGT and TBIL in the progression of SLE are opposite. High GGT level and low TBIL level might be risk factors for SLE aggravation. High GGT level and low TBIL level had a subadditive effect on the increased risk of SLE aggravation.